Breaking Cocoa, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
A picture of a group of labourers gathered around a large pile of cocoa pods with some sitting and breaking the pods to get the beans.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cocoa--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Working class--Trinidad and Tobago; Cocoa trade--Trinidad and Tobago; Cocoa processing--Trinidad and Tobago; 1908; Draft animals--Trinidad and Tobago; Donkeys--Trinidad and Tobago